Prevalence and associated factors of a repeat of suicide attempt among individuals attending an emergency department in Oman - Salim Al-Huseini; Mandhar Al maqbali; Hassan Mirza; Mahmood Al Khatri; Alkhatib Al Saadi; Moon-Fai Chan; Samir Al-Adawi (Discover Psychology)
Abstract Background This study aims to determine the rate of re-attempted suicide among individuals with a prior history of suicidal attempts. Additionally, it seeks to identify factors that could potentially predict future suicide re-attempts. Methods We retrospectively collected medical data on patients under 18 years of age who were admitted to our emergency department after attempting suicide. We evaluated the general characteristics of the patients. We divided them into two groups: patients who had made multiple suicide attempts and patients who attempted suicide for the first time. Logistic regression analysis was performed. Results A total of 154 patients who had previously attempted suicide and sought medical attention in the emergency department were included in the analysis. Among these patients, 55 individuals (35.7% of the participants) had a documented history of previous suicide attempts. Logistic regression analysis showed that patients with a diagnosed psychiatric disorder were 4.5 times more likely to attempt another suicide compared to those without such a condition (OR = 4.534, p = 0.002). Similarly, patients with a history of illicit drug use were 3.26 times more likely to attempt suicide again than those who reported no substance use (OR = 3.264, p = 0.036). Conclusion Individuals with a history of suicide attempts are at increased risk of further attempts. This study found that around 36% of people who had previously attempted suicide attempted additional attempts during the study. Moreover, factors such as substance use and a background of psychiatric disorders can predict the likelihood of re-attempting suicide.